Usefulness of Three-dimensional Stereoscopic Images for Cerebral Endovascular Treatment - Yagi, Ryokichi; Kawabata, Shinji; Ohnishi, Hiroyuki; Kuroiwa, Toshihiko; Miyachi, Shigeru; Hiramatsu, Ryo (Journal of Neuroendovascular Therapy, 2016)
Purpose: Reconstructed three-dimensional (3-D) images are essential for cerebral endovascular treatment. Conventional reconstructed 3-D images are no more than planar images projected onto a monitor. In this study, we prepared 3-D stereoscopic images before cerebral endovascular treatment, and conducted preoperative simulation to examine their usefulness (the subjects were six cases with cerebral aneurysms and eight with arteriovenous shunts).Case Presentations: Case 6: The patient was a 60-year-old male with an unruptured paraclinoid aneurysm. Case 8: The patient was a 64-year-old male with a spinal dural arteriovenous fistula. To prepare 3-D stereoscopic images, 3-D stereoscopic image-converting Work Station/a 3-D monitor was used. The first surgeon performed a preoperative simulation using 3-D stereoscopic images. Subsequently, usual cerebral endovascular treatment was conducted, and the usefulness of 3-D stereoscopic images was evaluated with free comments after surgery.Conclusion: The application of 3-D stereoscopic images for cerebral endovascular treatment was useful for recognition of spatial orientation. In particular, it was highly assessed in arteriovenous shunt disease patients with a complex vascular structure. Therefore, 3-D stereoscopic images may be appropriate for training for non-skilled specialists in cerebral endovascular treatment and student education.